HbA1c underperforms in identifying abnormal glucose tolerance in the presence of G6PD deficiency: Insight from the Africans in America study - Amy R. Bentley; Kauthrah Ntabadde; Claudine B. Kabeza; Kenneth Ekoru; Christopher W. DuBose; David B. Sacks; Adebowale A. Adeyemo; Charles N. Rotimi; Anne E. Sumner (PLoS ONE, 2026)
G6PD deficiency (G6PD-D) variants are associated with lower hemoglobin A1c (HbA1c) concentrations, raising concerns about the diagnostic efficacy of HbA1c for abnormal glucose tolerance (Abnl-GT) in Africans, in whom risk of G6PD-D and Abnl-GT is high. G6PD-D is assessed using genotyping or an enzymatic assay, but because G6PD-D is X-linked, the enzymatic assay is necessary for determining status for women heterozygous for deficiency variants. We assessed: 1) ability of HbA1c to detect Abnl-GT by G6PD-D; 2) concordance of genotyping and enzymatic assay for G6PD-D in sub-Saharan Africans living in the US. 534 participants of the Africans in America study were included, with HbA1c ranging from 3.1–11.3%. Abnl-GT determined by HbA1c (≥5.7%) was compared to the diagnostic standard, the oral glucose tolerance test (fasting glucose≥100 mg/dL and/or 2h glucose≥140 mg/dL). G6PD-D status was determined by genotype (n = 263), enzymatic assay (n = 83), or both (n = 188). G6PD-D could not be determined for 13 women heterozygotes with only genotype data. In the remaining participants, HbA1c was 0.9% lower among those with G6PD-D (4.6 ± 0.5; range 3.1–5.6) compared to those with normal G6PD activity (5.5 ± 0.6; range 4.2–11.3; P < 0.001). Glucose concentrations did not differ between groups. HbA1c sensitivity and specificity for Abnl-GT were 0% (0/17) and 100% (37/37) among those with G6PD-D, and 50% (98/195) and 80% (217/272) among those with normal activity. After excluding women heterozygotes, concordance for G6PD-D detection by genotype and the enzymatic assay was 100%. G6PD-D was associated with ~0.9% lower HbA1c in this study, leading to a failure of HbA1c to identify Abnl-GT in these participants. Such a dramatic difference in a screening tool could have consequences in practice, including late diagnosis, undertreatment, and increased complications among those with G6PD-D. Additionally, the results for the enzymatic assay were perfectly concordant with the genotype results for G6PD-D. However, as genotype alone cannot predict G6PD-D in heterozygous women, the enzymatic assay was more informative.